Auditing Information System : Delivery Product Service - Purwoko Purwoko (CommIT (Communication and Information Technology) Journal, 2011)
Purpose of the research is to ensure the securities of information system asset and to ensure if informa-tion system support the operational and data collected was valid. Research method that used in this research were library studies and field studies. Field studies such an observation, questioner, and inter-view. the expected result are founding the weakness of security management control, operational man-agement control, input control, and output control of risk happened in the company. Conclusion of this research are the system on the company work good and there’s no potential risk happened and make an impact to the delivery process of information system.Index Terms - Auditing Information system, Delivery product process.